The Experiences of Teachers at Multi Grade Classrooms at Special Education Schools - Khalid, Muhammad Usman; Manzoor, Afaf; Rashid, Asifa (Annals of Human and Social Sciences, 2024)
This study examines the experiences of teachers in multi-grade classrooms within special schools in Punjab, Pakistan. The aim is to identify the challenges and practices by the teachers during multi grade teaching. This was a descriptive study and quantitative method was used.Theresearch involved 230 participants as sample from special institutions in Punjab.Convenient sampling method was used to collect data. A self designed instrument was developed after intensive review of literature and validity from eminent field experts. Participants completed a survey questionnaire, and the collected data were analyzed using descriptive and inferential statistics. The findings indicate that teachers encounter significant challenges in multi-grade teaching within special schools, including managing different levels of learning, insufficient resources, lack of training, classroom management issues, instructional strategies, assessment difficulties, and curriculum concerns.The conclusions drawn suggested that addressing these challenges requires providing support, allocating resources, and improving classroom management practices. It also recommended enhancing professional development opportunities and designing a curriculum that promotes inclusivity and caters to the needs of students in multi-grade classrooms.